2018
DOI: 10.11159/ijepr.2018.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Operation Parameters on Heavy Metallic Ion Removal from Mine Waste by Natural Zeolite

Abstract: This study investigates the effects of particle size (0.420-1.sorption process is performed in batch mode with a 100 mL aqueous solution, acidified to a pH level of 2 with concentrated nitric (HNO3) acid. For all experimental parameter conditions examined, the removal efficiency order follows: Pb 2+ >>Fe 3+ >Cu 2+ >Zn 2+ >Ni 2+ ; the zeolite mineral exhibits the greatest preference towards the Pb 2+ ion in all parameter trends. Overall, the removal efficiency is increased with decreasing particle size, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…However, most elements were not detected after the filtrations, passing so it is assumed that the zeolite treatments eliminated some levels of these elements. For example, Ciosek and Luk (2018) found that zeolite was more effective in removing Pb 2+ than Fe 3+ , Cu 2+ , Zn 2+ and Ni 2+ .…”
Section: Other Metalsmentioning
confidence: 99%
“…However, most elements were not detected after the filtrations, passing so it is assumed that the zeolite treatments eliminated some levels of these elements. For example, Ciosek and Luk (2018) found that zeolite was more effective in removing Pb 2+ than Fe 3+ , Cu 2+ , Zn 2+ and Ni 2+ .…”
Section: Other Metalsmentioning
confidence: 99%